El análisis financiero como técnica de evaluación y planeamiento incide en la gestión financiera y económica de la Coopac Parroquia San Lorenzo para controlar la liquidez, la rentabilidad y el riesgo crediticio. - Lara Flores, Milton Eber (2016)
This work is an investigation that the COOPAC PARISH SAN LORENZO referred to help maintain good liquidity and credit risk through efficient management. Providing a useful framework for decision-making and achieve an efficient and effective financial management, enabling a better source of credit service of its partners. It was necessary to develop a situational analysis of the cooperative sector, to make a financial and economic analysis in the company and measure the level of management according to their goals set where it was shown that the management of the cooperative in the period 2014-2015, is acceptable. According to the results we can say that the COOPAC PARISH SAN LORENZO is in a regular situation of liquidity and profitability and makes a good credit risk management; so that decisions will be taken to allow the cooperative to improve competitiveness with social responsibility and the market; for it was recommended financial economic analysis permanently, have specialized personnel, to comply fully with the obligations of the FENACREP, implement a marketing area and expanding segment of the partners.